A CASE REPORT ON MATERNAL t (1;2) (q11; p11.1) AND ITS INHERITANCE - Posam, Pratibha Gopal; Sabnis, Dr. Anjali Satyen (International Journal of Research -GRANTHAALAYAH, 2021)
Balanced translocation in one of the partners may form faulty gametes and so it may be associated with infertility or recurrent miscarriages. Although, if same balanced translocation gets inherited then it gives rise to normal child. We report a case of non-consanguineous couple with the history of spontaneous abortion with bilateral dysplastic kidney in the foetus. Karyotyping of husband was normal and wife showed autosomal balanced translocation between q arm (11) of chromosome 1 and p arm (11.1) of chromosome 2. After doing genetic counselling for prenatal diagnosis, couple underwent prenatal diagnosis by chorionic villous and amniotic culture in two pregnancies respectively. In the first pregnancy, the female foetus inherited same translocation which mother carried and in the second pregnancy, male foetus inherited normal chromosomes from mother. Genetic counselling was done during both the pregnancies and couples continued the pregnancy. Inheritance of balanced translocation and normal chromosomes in next generation from mother having balanced translocation is rare to happen. Proper genetic for prenatal diagnosis will definitely help the couple to have normal children